The stone girl's story - Durst, Sarah Beth (Clarion Books/Houghton Mifflin Harcourt, 2018)
A girl made of stone, forever twelve years old, has outlasted the father who carved her and gave her life, but now the magical marks that animate her are fading and she must leave her mountain home and find help in the valley below if she wants her story--and those of her family--to continue.--Provided by Publisher.